Măsurarea sărăciei şi incluziunii sociale – un caz de asimilare selectivă a inovaţiei - Briciu, Cosmin (Calitatea Vieții, 2009)
The study illustrates the difficult process of adoption of social innovation within the structures of the decision-making system, frequently in a selective manner and lacking the guarantee of real sustainability. The case of the 2002 anti-poverty strategy, evaluated as a strategy with a high innovative potential, is discussed. The long term impact of the various components of the strategy is perceived as a heterogeneous one: while the institutional structure has been practically abandoned after the elections, the influence of the anti-poverty plan can be detected in other policy documents prepared afterwards. The methodological component, regarding the measurement of poverty and social inclusion, designed only as a tool for the strategy, has been adopted in a more visible and certifiable manner. The study suggests some of the possible explanations for the success and failure in the selective adoption, diffusion and sustainability of the different components of the strategy. In this context, the system of social inclusion and poverty indicators has become an agent for the diffusion and maintenance of the social innovation. The nature and the range of the social problems measured by the indicators press on decision-makers to address critical problems and widen the attention from the current problems, where resources are already planned and procedures are shaped, to the whole spectrum of their responsibilities.